How Nalco revitalized its quality process for R&D - Keiser, Bruce A.
Bruce A. Keiser and Natalie R. Blake describe the steps Nalco Chemical Co. took to develop a quality improvement process that met the company's own needs.
As they focus on 'doing it the right way the first time,' researchers are making more measurements and generally becoming more innovative.
Nalco Chemical Company began its "quality journey" in 1986 by adopting parts of several Quality philosophies. Among these are the Deming measurement systems and the Juran problem-solving methodology. Yet, the Quality Process in research and development was sporadic. Change was needed to make it applicable to this discipline. The modification process followed seven steps consisting of: defining the problem, planning the solution, implementing a quick fix, identifying the root causes, taking corrective action, evaluating the corrective action and holding the gains. At each step, tools (e.g. measurement, Pareto diagrams, process modeling) were applied. The tools focused attention on the root causes and guided the corrective actions. Some of the changes included : adoption of Quality Principles for Research and Development, and changes in recognition, measurement and communications. The end result was a Quality Improvement Process leading research and development to "do it the right way the first time."
Keywords: Quality process